Natural Resource Rent and Financial Development: Testing Financial Resource Curse Hypothesis in Iran - Majid Aghaei; Mahdieh Rezagholizadeh; mohammad abdi; rawa mosavi (پژوهشهای اقتصادی)
Aim and Introduction: Based on empirical studies, in addition to the natural resources curse and the negative impact of natural resources income on the economic growth and development in resource-rich countries, some of these countries face various other issues. These issues include political and social problems, high levels of poverty and inequality, low levels of education, economic growth fluctuations, low institutional quality, and political instability (Sachs & Warner, 2001). In this context, one of the challenges in resource-rich countries, especially in developing countries, when compared to countries without natural resources, is the low level of financial development. Financial development has failed to play an effective role in the economic growth of these countries (Albadawi and Soto, 2012; Gelb, 2010; Samargandi et al., 2014; Frenkel, 2012).  On the other hand, considering studies such as those by Pendergas et al., (2011), in most resource-rich countries that have managed to overcome the resource curse, a reasonable level of financial development is observed. Therefore, the first question that arises is whether there is a relationship between financial development and the abundance of natural resources in these countries. Given the role of the financial system in the optimal allocation of resources, what impact will the financial system have on the abundance of natural resources in resource-rich countries? Iran is a country abundant in oil resources that has struggled to overcome the challenges and obstacles on the path to development, such as unemployment and economic growth fluctuations. Issues related to natural resources still persist in this country. Given the importance of the relationship between the financial sector and the abundance of natural resources for necessary policymaking on the path to economic growth and development, this study aims to examine and investigate the relationship between the abundance of natural resources and financial development in Iran using various financial development indicators and different econometric methods. Methodology: In order to investigate and empirically analyze the long-term and short-term dynamic relationship between variables, this research employs the Autoregressive Distributed Lag (ARDL) bounding test approach. The ARDL Bounding test method was developed by Pesaran and Shin (1999) and Pesaran et al. (2001). This method offers advantages over other conventional and previous cointegration methods, such as the Johansen and Toda-Yamamoto approaches. Some of its advantages include applicability regardless of considering the order of cointegration between variables, its ability to handle cases where variables are I (0) or I (1), suitability for limited sample sizes, obtaining efficient estimates without the risk of over-specification of the long-run model relationships, and presenting a reduced-form single-equation form rather than a systemic one for the long-run relationship. The ARDL model estimates the short-term and long-term linear relationship between variables and cannot estimate non-linear relationships between the variables. Therefore, in this study, considering the possibility of a non-linear and asymmetric relationship between resource rents and financial development, the non-linear ARDL model, developed by Shin et al. in 2014, was employed to estimate the model. The NARDL model is a specific form of the ARDL model developed by Pesaran et al., (2001). It allows for the investigation of asymmetry in the long-term and short-term relationships between variables. The advantage of the NARDL method over other cointegration techniques is its superior performance in models with limited observations. Furthermore, this approach is applicable when the explanatory variables in the model are endogenous (Alam and Quazy, 2003). Findings: Results indicate that impact of natural resource abundance on the banking development index is not significant in the short term, while the lagged values of natural resources have a positive and significant impact on the banking development index in Iran. Considering the long-term estimation of the model, it can be concluded that the effect of natural resource abundance or, in other words, resource rents on banking sector development in Iran is positive and significant. Based on this result, the hypothesis of resource curse in the banking sector during the examined period in Iran is confirmed. Beck (2011) found that in natural resources rich countries, banks have better capitalization and profitability, but they provide fewer credits to the private sector and have less inclination towards financial development. Therefore, it appears that due to the bank-oriented nature of the financial system in Iran and the substantial injection of oil resources into banks, it has managed to foster the development of this sector. The results of estimating the stock market development model indicate that natural resource abundance has a positive impact on stock market development in both the short and long terms, although it is not statistically significant. Therefore, it is not possible to make a clear statement about the presence or absence of the resource curse in the stock market. Based on studies like Asif et al. (2020) and Ali et al. (2022), the inclusion of various companies related to natural resources in the stock market can help finance these companies in their high-cost extraction and refining operations. Consequently, it can create various job opportunities and boost economic activities, leading to economic growth and development. Therefore, income derived from natural resources through an efficient stock market can contribute to economic growth. The impact of natural resource abundance on the overall financial development index in the long term is positive but not statistically significant. Therefore, the hypothesis of the resource curse in Iran is not confirmed. Considering that the Iranian financial system is influenced by the banking system, and resource rents have been confirmed in the banking sector, this result can be justified as indicative of the greater flow of oil revenues into the Iranian banking system. However, this result may also indicate the dominant role of the government in the allocation of natural resource revenues and the weakness of the private sector and the capital market in the proper allocation of these revenues. The results of estimating the overall financial development index, which is obtained by combining stock market development and banking development, highlight the importance of financial integration and the utilization of the entire financial system's capacity to transform resource rents into a resource blessing.Top of Form Discussion and Conclusion: Based on the empirical results, the hypothesis of the presence of resource cures in the banking sector in Iran was confirmed, given the significant positive relationship between banking sector development and natural resource abundance during the study period. However, regarding the resource curse in the stock market, it is not possible to make a clear statement due to the insignificance of the coefficients. According to the estimation of the NARDL model and the significant positive impact of positive shocks from natural resource rents on the banking development index on one hand, and the negative (although insignificant) impact of negative shocks on the other hand, the results of the NARDL model can be seen as confirming the findings of the ARDL model. Therefore, the hypothesis of resource blessing in the banking sector is cautiously confirmed based on this model. In the case of the stock market, the NARDL results also do not provide conclusive evidence regarding the hypothesis of a resource curse in Iran's stock market due to the insignificance of the coefficients related to resource rents in the estimation of the stock market development index. The results of the NARDL estimation in the overall financial development index model indicate that positive shocks from resource rents have a significant positive impact on the overall financial development, while negative shocks have a negative impact, although they are not statistically significant. Considering these results, the dominant role of the banking system in Iran's financial system is confirmed, and thus, special attention from the government to the capital market as one of the most effective components of the financial system seems necessary.Top of Form